Вамыш: очеркъёс / Георгий Грязев - Грязев Георгий Геннадьевич (Удмуртия, 2014)
Экземпляры: КО (20151204) / Инвентарный номер: 52197 / Цена: 100.00. / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: Г 92 / ГРНТИ: 17.82.40 / ББК: 63.3(2Рос. Удм)